The Alleviating Effect of Brassinosteroids on Cadmium Stress in Potato Plants: Insights from StDWF4 Gene Overexpression - Xiangyan Zhou; Rong Miao; Jiaqi Luo; Wenhui Tang; Kexin Liu; Caijuan Li; Dan Zhang (Agronomy, 2025)
The potato is the fourth largest cultivated crop worldwide. Soil cadmium (Cd) pollution poses a significant threat to crop growth. Brassinosteroids (BRs) play a significant part in enhancing plant resistance against abiotic stresses. The DWF4 (dwarf4) gene is one of the rate-limiting enzyme genes involved in the synthesis of BRs. This study employed seedlings of transgenic potatoes overexpressing the StDWF4 gene (OE) and wild-type (WT) potatoes to clarify their alleviating effect on Cd stresses. The differences in phenotype, ultrastructure, physiological indicators, and plant hormone levels of Cd2+-treated potatoes were analyzed. The molecular mechanism of potatoes’ response to Cd2+ stress was revealed by transcriptomics. Results showed that the dry weight, fresh weight, plant height, root length, and stem diameter of OE potatoes under Cd stress were significantly higher than those of WT potatoes. Ultrastructural analysis revealed that the mitochondria, cell walls, and cell membranes of WT were more fragile than those of OE under Cd stress. The Cd2+ concentration in OE was always lower than that in WT, and both concentrations increased gradually as the duration of Cd2+ treatment was prolonged. The 24-epibrassionlide (EBL) content in OE was higher than that in WT. RNA-seq analysis manifested that the gene expression levels of OE and WT plants changed significantly under Cd2+ treatment. The differentially expressed genes (DEGs) were primarily connected to the moderation of the metabolic pathways, biosynthesis of secondary metabolites, phenylpropanoid biosynthesis, and plant hormone signal transduction. These findings indicated that overexpression of the StDWF4 gene in potatoes enhanced their alleviating effect on Cd stresses.